Impact of state and trait anxiety severity on retention and phase advancement in an outpatient buprenorphine treatment program. Issue 3 (3rd March 2022) - Gokarakonda, Srinivasa B.; Boydstun, Jacob M.; Yilanli, Musa; Han, Xiaotong; Kumar, Nihit; Oliveto, Alison H.; Mancino, Michael J.
Abstract: Background and Objectives: Comorbid anxiety is common among buprenorphine patients and may lead to poorer outcomes. This study aimed to examine the prevalence and impact of anxiety severity, measured by the State‐Trait Anxiety Inventory (STAI) form Y‐1 & Y2 scale, on treatment outcomes (retention and phase advancement) among outpatient buprenorphine‐treated patients. Methods: A retrospective chart review of 94 patients admitted to an outpatient buprenorphine treatment program was conducted. Patients were dichotomized into high and low severity groups based upon an STAI State Anxiety (S‐Anxiety) and STAI Trait Anxiety (T‐Anxiety) score ≥60 and <60, respectively. Associations of anxiety severity on successful phase advancement and retention during the first 90 days of treatment were assessed. Results: Twenty‐one of 94 (22%) participants reported high S‐Anxiety and had a significantly greater likelihood of phase advancement (OR = 12.80, 95% CI = [1.19, 136.71]) than those with low S‐Anxiety. No significant associations were found between either S‐Anxiety or T‐Anxiety and treatment retention. Current alcohol use and UDS negative test results for THC or amphetamines were each associated with phase advancement. THC negative UDS test results were associated with 90‐day treatment retention. Discussion and Conclusions: Contrary to prior reports, buprenorphine patients with higher state anxiety severity demonstrated similar retention and more rapid phase advancement than those with lower state anxiety severity. Scientific Significance: To our knowledge, this is the first study to quantify current anxiety severity using the STAI scale and evaluate its impact on treatment outcomes among buprenorphine‐treated patients.